How much might human capital policies affect earnings inequalities and poverty? - Jere R. Behrman (Estudios de Economía, 2011)
Economic inequality and poverty have persisted in Latin America despite important changes in political and policy regimes. This paper explores the relationship between various human capital programs aimed to reduced poverty and how improvements of those in poverty in the left tail of the earning income distribution are likely to reduce inequality. First it reviews some recent benefit/cost estimates for human capital intervention in LAC, suggesting some investments in which the returns appear quite high. Then it turns over to how much increases in schooling attainment targeted to the poor would reduce poverty and income inequality. This is illustrated empirically using the 2004 Chilean Social Protection Survey data. Alternative simulations suggest significant impacts of well targeted increases in schooling attainment on reducing poverty and inequality.
Keywords: I24; I3; J24; 330; inequality; poverty; human capital; Armut; Einkommensverteilung; Humankapital; Lateinamerika